Metodologias laboratoriais para o diagnóstico de hemoglobinas variantes - Chinelato-Fernandes, Ana R. [UNESP]; Domingos, Claudia R. B. [UNESP] (My University, 2006)
Among the electrophoretical methodologies for hemoglobin examinations under different experimental conditions, isoelectrofocusing and high performance liquid chromatography are the most frequently used for the detection of hemoglobin variants. Moreover, molecular techniques are also developed in many laboratories. The correct laboratorial diagnosis of hemoglobin alterations is especially important for the interactive forms principally in Brazil, because of the many associations of hemoglobin alterations and variants with co-migration. The association of classical and molecular techniques is essential for accurate identification of hemoglobin variants.
The laboratory methodology for diagnosis of hemoglobin variants
Keywords: Hemoglobinopathies; Hemoglobinopathy diagnosis; Methodologies association